2009
DOI: 10.1007/s10903-009-9246-7
|View full text |Cite
|
Sign up to set email alerts
|

Assess the Effects of Culturally Relevant Intervention on Breast Cancer Knowledge, Beliefs, and Mammography Use Among Korean American Women

Abstract: A pre-post test, two-group study was conducted to examine the effects of a culturally competent targeted intervention titled GO EARLY Save Your Life on the breast cancer and early screeningrelated knowledge and beliefs and mammography use among 180 Korean American (KA) women aged 40 years or older who had not had mammograms within the past 12 months. The intervention group received an interactive education session focused on breast cancer, early screening guidelines, and beliefs (breast cancer-related and Kore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…It was found that although education increased knowledge, it did not increase uptake of mammography screening. (Kim et al, 2010) However in a another study knowledge about mammography testing was significantly associated with the practice of mammography (Al-Naggar and Bobryshev, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that although education increased knowledge, it did not increase uptake of mammography screening. (Kim et al, 2010) However in a another study knowledge about mammography testing was significantly associated with the practice of mammography (Al-Naggar and Bobryshev, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Despite problems that emerged during cognitive interviews, the PI decided to retain all the items of Powe's cancer fatalism scale because (a) Powe's cancer fatalism items have proven to be effective in identifying cancer fatalism among other racial/ethnic groups, 6,32,33 (b) problems with Powe's cancer fatalism scale have never been reported in the literature, and, finally, (c) the PI wanted to measure differences in fatalistic attitudes between KAs and other racial/ethnic groups by comparing our study results with other studies using Powe's cancer fatalism scale.…”
Section: Cognitive Interviewsmentioning
confidence: 99%
“…This finding is different from previous findings because, in those studies, these items were key factors reflecting a lack of preventive orientation. 6,55Y58 In addition, a study by Russell et al (2003) on breast cancer screening among African Americans and whites reported that EFA factor loadings on these items were greater than 0.40. There are 2 possible explanations for these items performing so poorly in the current study.…”
Section: Internal Consistency Reliabilitymentioning
confidence: 99%
“…Chinese American women have reported that cancer is caused by diet (Simpson, 2003), immoral behavior (Wong-Kim et al, 2003), fate (Wong-Kim et al, 2003), and accumulation of anger (Simpson, 2003). Similarly Korean Americans believe that diseases, including cancer, are caused from excess negative forces such as chronic anger, misconduct, negative attitudes, or stress (Kim, Menon, Wang, & Szalacha, 2010). Latinas, primarily of Mexican American descent, report that diet (e.g., spicy foods, pork, food preservatives), tobacco, alcohol, caffeine, heredity, breast trauma (Hubbell, Chavez, Mishra, & Valdez, 1996; Thiel de Bocanegra, Trinh-Shevrin, Herrera, & Gany, 2009), birth control pills (Borrayo, Buki, & Feigal, 2005), and lack of, or insufficient, breastfeeding (Thiel de Bocanegra et al, 2009) are causal factors of cancer.…”
Section: Culture Health Beliefs and Health Behaviorsmentioning
confidence: 99%